An MRI-compatible varus–valgus loading device for whole-knee joint functionality assessment based on compartmental compression: a proof-of-concept study - Said, Oliver (MAGMA, 2020)
OBJECTIVE: Beyond static assessment, functional techniques are increasingly applied in magnetic resonance imaging (MRI) studies. Stress MRI techniques bring together MRI and mechanical loading to study knee joint and tissue functionality, yet prototypical axial compressive loading devices are bulky and complex to operate. This study aimed to design and validate an MRI-compatible pressure-controlled varus–valgus loading device that applies loading along the joint line. METHODS: Following the device’s thorough validation, we demonstrated proof of concept by subjecting a structurally intact human cadaveric knee joint to serial imaging in unloaded and loaded configurations, i.e. to varus and valgus loading at 7.5 kPa (= 73.5 N), 15 kPa (= 147.1 N), and 22.5 kPa (= 220.6 N). Following clinical standard (PDw fs) and high-resolution 3D water-selective cartilage (WATSc) sequences, we performed manual segmentations and computations of morphometric cartilage measures. We used CT and radiography (to quantify joint space widths) and histology and biomechanics (to assess tissue quality) as references. RESULTS: We found (sub)regional decreases in cartilage volume, thickness, and mean joint space widths reflective of areal pressurization of the medial and lateral femorotibial compartments. DISCUSSION: Once substantiated by larger sample sizes, varus–valgus loading may provide a powerful alternative stress MRI technique. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10334-020-00844-6) contains supplementary material, which is available to authorized users.